Optimization of the electrical performances in Solid Oxide Fuel Cells with room temperature sputter deposited Gd0.1ce0.9o1.95 buffer layers by controlling their granularity via the in-air annealing step. (28th April 2020) - Coppola, Nunzia; Polverino, Pierpaolo; Carapella, Giovanni; Sacco, Chiara; Galdi, Alice; Montinaro, Dario; Maritato, Luigi; Pianese, Cesare
Abstract: Using room temperature sputtering, we have deposited Gd0.1 Ce0·9 O1.95 buffer layers at the cathode/electrolyte interface of 10 cm 2 circular Solid Oxide Fuel Cells. By suitably selecting the in air annealing step, we show the possibility to control the granular properties of the Gd0.1 Ce0·9 O1.95 buffer layers in order to optimize the Solid Oxide Fuel Cell's electrical performances. In particular, we maximise the buffer layer grain density via an annealing process with a plateau temperature of 800 °C, obtaining improvements in the final Solid Oxide Fuel Cell performances with an 8% increase in the current density at 800 mV and 700 °C with respect to the Solid Oxide Fuel Cell annealed at 1050 °C, and with a 59% increase in the current density at the same voltage and temperature when compared to the standard cells with the Gadolinium Doped Ceria buffer layer produced by lithographic processes. The achieved optimization procedure clearly illustrates the potentiality of the room temperature sputtering process followed by in-air annealing step in the control of the granularity of the deposited layers. Moreover, the obtained results open the way to further studies about the industrial scalability of the used technique and to its implementation in practical large scale cell production process. Graphical abstract: Image 1 Highlights: Gadolinium Doped Ceria barrier layer deposited by Room temperature Sputtering. Physical Vapor Deposition technique applied to Solid Oxide Fuel Cells. Grain size control in Gadolinium Doped Ceria achieved through in air annealing step. Fuel cell performance optimized by tuning the grain size. Maximum performance gain at T = 700 °C with j = 0.86 A cm −2 and V = 800 mV.